Don't fear the Reaper [large type] - Jones, Stephen Graham, 1972- (Jones, Stephen Graham, 1972- Indian Lake trilogy, 2023)
"December 12th, 2019, Jade returns to the rural lake town of Proofrock the same day as convicted Indigenous serial killer Dark Mill South escapes into town to complete his revenge killings, in this riveting sequel to My Heart Is a Chainsaw from New York Times bestselling author, Stephen Graham Jones. Four years after her tumultuous senior year, Jade Daniels is released from prison right before Christmas when her conviction is overturned. But life beyond bars takes a dangerous turn as soon as she returns to Proofrock. Convicted Serial Killer, Dark Mill South, seeking revenge for thirty-eight Dakota men hanged in 1862, escapes from his prison transfer due to a blizzard, just outside of Proofrock, Idaho. Dark Mill South's Reunion Tour began on December 12th, 2019, a Thursday. Thirty-six hours and twenty bodies later, on Friday the 13th, it would be over"--